A Kinetic study of Tb3+ and Dy3+ co-substituted CoFe2O4 spinel ferrites using temperature dependent XRD, XPS and SQUID measurements. Issue 10 (July 2020) - Ikram, Salma; Jacob, Jolly; Mahmood, K.; Mehboob, Khurram; Maheen, Mutaiba; Ali, A.; Amin, N.; Hussain, Sajad; Ashraf, Fouzia; Ilyas, S.Z.
Abstract: In this research work, we have investigated the structural development of Tb 3+ and Dy 3+ co-substituted CoFe2 O4 ferrites using temperature and time dependent XRD measurements. Sol-gel auto combustion technique was used to synthesized Tb 3+ and Dy 3+ co-substituted spinel ferrites with composition CoFe2-x-y Tbx Dyy O4 (x + y = 0.0–0.25). Various characterization techniques such as High temperature XRD, XPS and SQUID were used to observe the Kinetics mechanism as well as the impact of co-substitution on the structural and magnetic properties. Room temperature XRD scans showed that the synthesized materials having single phase and were crystalline in nature. The crystallite size was lied in nano regime ranging from 26.07 to 21.92 nm and lattice parameters were found to be decreased with increasing rare earth metal ions contents. Temperature and time dependent XRD data suggested that structure of investigated samples not degrade even at temperature 900 °C which was maintained for 2 h. The ionic states of Co 2+, Tb 3+, Dy 3+ and Fe 3+ were confirmed by X-ray Photoelectron spectrometry measurements along with the binding energies of Co2p, Tb 2p, Dy 2p, Fe 2p which confirmed the tetrahedral and octahedral sites for substituted ions. Room temperature magnetic measurements of annealed nanoferrites were carried out by operating the SQUID magnetometer in VSM mode. The data demonstrated that increasing concentrations of substituent (Tb 3+ and Dy 3+ ) resulted in the reduction of various magnetic parameters such as remanence, saturation magnetization and Coercivity. The calculated values of saturation magnetization and coercivities were found in the range of 78.1–45.15emu/g and 742–543Oe respectively. This study concluded that cation distribution and crystallite size is effective in controlling the structural, morphological and magnetic properties.